ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE, LEVERAGE, ASIMETRI INFORMASI DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa EfekInd - Eneng Elawati (AKT 16 UMY 141, 2016)
This study aimed to examine the effect of corporate governance mechanisms, the leverage, asymmetry information, and the size firm earning management. Earning management calculated using discretionary accruals, whereas mechanism corporate governance variables determined by the Audit Committee, board size, proportion commissioner Tbk, and institutional ownership. Industry specialists KAP The proxy with audito industry specialists. Leverage is calculated using total debt ratio. Information asymmetry relative calculated using bid-ask spread. Company size is measured using the natural logarithm with of total sales perusahaa. Sample research singer manufacturing company is listed in Indonesia Stock Exchange (BEI) on year 2012-2014. The sample data tin from 69 companies that was taken through purposive sampling. Methods of research singer analysis using multiple regression analysis using SPSS and the process. Results of this study showed that the audit committee is not an effect against earning management, board size has positive effect against earning management, the proportion commissioner Tbk no effect against earning management, institutional ownership has an effect against earning management, industry specialists KAP no effect against earning management, leverage positive effect against earning management, information asymmetry does not affect the earning management, and size firm does not affect the earning management. Keywords: Mechanism of corporate governance, leverage, asymmetry information, the size firm, earning management.